Auditory spatial concepts in blind football experts. (January 2016) - Velten, Marcella C.C.; Ugrinowitsch, Herbert; Portes, Leonardo L.; Hermann, Thomas; Bläsing, Bettina
Abstract: Objectives: We compared the spatial concepts given to sounds' directions by blind football players with both blind non-athletes and sighted individuals. Method: Participants verbally described the directions of sounds around them by using predefined spatial concept labels, under two blocked conditions: 1) facing front, 2) pointing with the hand towards the stimulus. Results: Blind football players categorized the directions more precisely (i.e., they used simple labels for describing the cardinal directions and combined labels for the intermediate ones) than the other groups, and their categorization was less sensitive to the response conditions than blind non-athletes. Sighted participants' categorization was similar to previous studies, in which the front and back regions were generally more precisely described than the sides, where simple labels were often used for describing directions around the absolute left and right. Conclusions: The differences in conceptual categorization of sound directions are a) in sighted individuals, influenced by the representation of the visual space b) in blind individuals, influenced by the level of expertise in action and locomotion based on non-visual information, which can be increased by auditive stimulation provided by blind football training. Highlights: We studied the categorization of sound directions (CSD) in blind football experts. CSD of blind athletes was compared to blind non-athletes and sighted participants. Blind athletes' CSD was more precise than the two other groups. Blind athletes' CSD was more consistent than blind non-athletes'. Differences reflect sight conditions and expertise in auditory-based orientation.